Analisis Daya Dukung Perairan Puhawang untuk Kegiatan Budidaya Sistem Karamba Jaring Apung - Herman Yulianto; Nikky Astiastari; Abdullah Aman Damai (AQUASAINS, 2015)
Puhawang Island have a potency to developed for aquaculture especially cage system. Aquaculture with cage system will be an optimum production if the environment still support for fish to growth. Environment faktor that support the growth of fish and production of cage system called carrying capacity. The aim of this research was to determined the ability of waters around Puhawang Island to support cage system especially for cultivated grouper with floating net cages. This research was conducted using descriptive method in August to September 2014. The result shown that water quality in Puhawang Island still suitable for cage system. Holding capacity could be optimized to 53.550 tons ( with carrying density is 107.100.000 of fish). This production could be reach if used 39.600 units with 6x6x3m in volume dimension, and maksimum density is 25 fish each unit cage